2013
DOI: 10.1002/humu.22489
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations of Inhibins in Early‐Onset Ovarian Epithelial Tumors

Abstract: To identify novel genetic bases of early-onset epithelial ovarian tumors, we used the trio exome sequencing strategy in a patient without familial history of cancer who presented metastatic serous ovarian adenocarcinomas at 21 years of age. We identified a single de novo mutation (c.1157A>G/p.Asn386Ser) within the INHBA gene encoding the βA-subunit of inhibins/activins, which play a key role in ovarian development. In vitro, this mutation alters the ratio of secreted activins and inhibins. In a second patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Secreted activin A can be detected in both the serum and body fluid of affected patients (12)(13)(14). Consistent with the hypothesis that activin biology is important in gynecologic cancer, germline mutations in genes encoding activin and inhibin subunits (INHBA and INHA) have been described in women with young onset ovarian cancers, raising the question that in some settings, alteration of this pathway may play a role in tumorigenesis and inherited mutations may confer cancer susceptibility risk (15). These mutations are believed to disrupt activin and inhibin production, altering the ratio of activin and inhibin in favor of epithelial ovarian cell growth.…”
Section: Introductionmentioning
confidence: 71%
“…Secreted activin A can be detected in both the serum and body fluid of affected patients (12)(13)(14). Consistent with the hypothesis that activin biology is important in gynecologic cancer, germline mutations in genes encoding activin and inhibin subunits (INHBA and INHA) have been described in women with young onset ovarian cancers, raising the question that in some settings, alteration of this pathway may play a role in tumorigenesis and inherited mutations may confer cancer susceptibility risk (15). These mutations are believed to disrupt activin and inhibin production, altering the ratio of activin and inhibin in favor of epithelial ovarian cell growth.…”
Section: Introductionmentioning
confidence: 71%
“…We found familial ovarian cancer patients who were diagnosed before 55 years of age had consistently significantly higher risk of death in the 5 years after the cancer diagnosis compared to patients with sporadic cancer. This might be due to germline mutations relevant to ovarian cancer . A contributing factor to the differences in survival for familial and sporadic cases of ovarian cancer is the distribution of histological types.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to germline mutations relevant to ovarian cancer. 41 A contributing factor to the differences in survival for familial and sporadic cases of ovarian cancer is the distribution of histological types. In agreement with previous studies, 42 we found serous ovarian cancer to be more familial than other histological types and BRCA1 or BRCA2 carriers are more likely to have this histology.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Unlike many other molecules that are being used -or have been considered -as targets for cancer therapy, activin A is not a clear oncogenic driver. Although it is overexpressed in many cancer types, mutations or gene amplification are very rare and its receptors and downstream signaling mediators show loss-offunction mutations rather than gain-of-function mutations [38,127]. Impairment of tumor cell growth and decreased tumor cell migration and invasion have been achieved by activin A signaling inhibition in experimental settings, but it is still unclear whether blockade of activin A signals alone will be sufficient to achieve tumor shrinkage or reduction of metastasis in patients.…”
Section: Expert Opinion: Perspectives and Challenges For Targeting Acmentioning
confidence: 99%